(untitled) (Research, Society and Development, 2021)
Introduction: Photodynamic Therapy is an oxygen-dependent photochemical reaction initiated by a low-power laser with an appropriate wavelength. And it has been widely used in periodontics because it allows the reduction of periodontopathogens with no systemic side effects and minimal possibilities of bacterial resistance. Objective: To carry out a literature review on photodynamic therapy and its importance in the treatment of periodontal diseases. Methodology: A literature search was carried out in the Pubmed, Scielo and Lilacs databases, with the help of the following health descriptors: “Photodynamic Therapy” (Photodynamic Therapy); “Photochemotherapy” (Photochemotherapy); “Low Power Laser Therapy” between 1991 and 2021. Results: Looking at the facts, it was seen that choosing one of a photosensitizers and applying it with a correct and specific wavelength leads to the success of this therapy. Conclusion: It is necessary to carry out more studies aimed at its use in the treatment of periodontal diseases. Specific therapeutic protocols are defined that allow its execution based on science.